A method for preparing polyurethane shape memory fabric for fireproofing material
Patent Information
- Application Number
- CN202611443342.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]为了克服背景技术中提到的现有形状记忆织物在防火材料应用中存在的涂层易脱落、高温循环稳定性差、面料僵硬、与高性能纤维基底适配性差等缺陷,本发明提供了一种用于防火材料的聚氨酯形状记忆织物制备方法,能够有效解决上述背景技术中涉及的问题
1、该一种用于防火材料的聚氨酯形状记忆织物制备方法,在形状记忆聚氨酯基体中引入磷-氮膨胀型阻燃剂,经共混均匀分散于聚合物网络内部,阻燃剂不参与交联反应,不影响聚氨酯可逆相结构的完整性,同时赋予织物高效阻燃特性,形状记忆聚氨酯提供热致形变响应能力,膨胀型阻燃剂在受热时形成致密碳层发挥隔热隔氧作用,二者协同共存,使织物兼具优异的热响应形变功能与阻燃防护功能,满足防火材料对智能变形与安全防护的双重需求。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of intelligent textile functional materials and safety protection materials, and in particular to a method for preparing polyurethane shape memory fabric for fireproof materials. Background Technology
[0002] Fireproof materials are the core barrier to ensure personnel safety in high-temperature operation scenarios such as fire fighting, metallurgy, and petrochemicals. With the development of intelligent wearable protective equipment, modern fireproof materials not only need to have excellent flame-retardant and heat-insulating properties, but are also expected to have heat-responsive intelligent deformation functions. For example, they can actively change the gap between the fabric and the human body in a high-temperature environment to form an air insulation layer, or automatically unfold to form a fireproof cover in a high-temperature environment. Shape memory fabrics, as a type of stimulus-responsive intelligent textiles, can meet the above-mentioned heat-induced deformation requirements.
[0003] Existing shape memory fabrics mainly employ post-treatment coating methods, but these methods present the following problems in fire-retardant applications: Impregnation under normal pressure results in shape memory resin adhering only to the fiber surface, with weak interfacial bonding with high-performance fiber substrates such as polyimide and aramid, which have high surface inertness. After high-temperature shrinkage and expansion or washing, the coating is easy to fall off, and the memory function quickly fails. In addition, direct high-temperature curing causes solvent to evaporate too quickly, resulting in surface film formation and incomplete internal cross-linking. The resin is prone to secondary degradation or softening in high-temperature environments, leading to a decrease in shape recovery rate and insufficient thermal cycling stability. Moreover, existing formulations focus on memory function while neglecting flexibility and breathability, affecting work comfort. At the same time, existing processes have poor compatibility with high-temperature resistant synthetic fiber substrates, making it difficult to adapt to mainstream fire-retardant fabric systems. Summary of the Invention
[0004] In order to overcome the defects of existing shape memory fabrics in fire-retardant applications, such as easy coating peeling, poor high-temperature cycling stability, stiff fabric, and poor compatibility with high-performance fiber substrates, as mentioned in the background art, this invention provides a method for preparing polyurethane shape memory fabrics for fire-retardant materials, which can effectively solve the problems mentioned in the background art.
[0005] The objective of this invention can be achieved through the following technical solution: This invention provides a method for preparing polyurethane shape memory fabric for fire-retardant materials, comprising the following steps: Step 1: Pretreatment of fabric substrate material: Prepare the substrate material for the polyurethane shape memory fabric, namely the high temperature resistant fabric substrate, and clean and dry the high temperature resistant fabric substrate to remove surface impurities and control the fabric moisture content to be lower than the set value for later use. Step 2: Prepare a shape memory modification solution for finishing and modifying a high-temperature resistant fabric substrate: Dissolve polycarbonate diol (PCDL) in a dried polar organic solvent, add 4,4'-diphenylmethane diisocyanate (MDI) and a catalyst to carry out a prepolymerization reaction to obtain a prepolymer solution. Separately, dissolve a chain extender and a crosslinking agent in a polar organic solvent, add the prepolymer solution to carry out a chain extension and crosslinking reaction to obtain a shape memory polyurethane adhesive. Disperse an intumescent flame retardant in a polar organic solvent to form a flame retardant slurry. Blend the flame retardant slurry with the shape memory polyurethane adhesive, and after degassing and filtration, obtain a uniform and stable flame retardant shape memory modification solution. Step 3, Negative pressure impregnation finishing: Immerse the pretreated fabric base material in Step 1 in the flame-retardant shape memory modified liquid obtained in Step 2, and perform impregnation treatment under negative pressure to allow the flame-retardant shape memory modified liquid to penetrate into the fibers of the fabric base material. After removal, roll to control the liquid retention rate and let stand to remove excess residual liquid. Step 4, Heat treatment and shaping: The fabric treated in step 3 is subjected to gradient heating pre-drying, high-temperature curing and cross-linking and low-temperature constant temperature activation treatment in sequence, so that the shape memory polyurethane cross-links in situ inside the fabric fibers to form a stable and reversible memory network, thus obtaining the polyurethane shape memory fabric used for fireproof materials.
[0006] Preferably, the shape memory modified liquid comprises the following raw material components in parts by weight: 5-20 parts of polycarbonate diol (PCDL), 6-12 parts of 4,4'-diphenylmethane diisocyanate (MDI), 0.05-0.5 parts of dibutyltin dilaurate (DBTDL), 130-500 parts of N,N-dimethylformamide (DMF), 0.5-1.28 parts of hydroquinone dihydroxyethyl ether (HQEE), 1-5 parts of 1,4-butanediol (BDO), 0.10-0.18 parts of trimethylolpropane (TMP), 0.5-5 parts of ammonium polyphosphate (APP), 0.2-3 parts of pentaerythritol (PER), and 0.2-3 parts of melamine (MEL); DMF, as a high-boiling-point polar anhydrous solvent, disperses the heat of polymerization and reduces the viscosity of the system. PCDL, as a long-chain flexible soft segment, provides freely moving molecular chains at low temperatures and is the core source of thermal response shape memory deformation and high hydrolysis resistance. MDI, a diisocyanate monomer, constructs a microphase region containing a benzene ring rigid hard segment to fix the permanent shape of the material and acts as a molecular bridging unit to build the polyurethane polymer backbone. N,N-dimethylformamide is a polar organic solvent that is dehydrated by activated molecular sieves before use. Dibutyltin dilaurate is a catalyst, which, as an organotin catalyst, enables the system to... The reaction is carried out at a low temperature of 75~78℃ to avoid yellowing at high temperatures and thermal degradation of raw materials. The chain extender is a compound of hydroquinone dihydroxyethyl ether and 1,4-butanediol. The former improves the crystallinity of hard segments and memory recovery efficiency, while the latter improves the elongation at break and bending flexibility of the material. The trimethylolpropane is a crosslinking agent. As a mild chemical crosslinking agent, it introduces a covalent crosslinking network, restricts the slippage of polymer chains, and greatly improves the memory cycle stability and heat aging resistance, so as to meet the requirements of multiple thermal deformation of fireproof materials. The intumescent flame retardant is a phosphorus-nitrogen intumescent system composed of ammonium polyphosphate, pentaerythritol and melamine.
[0007] Preferably, step 1 specifically includes the following steps: Select polyimide plain weave fabric or aramid fabric as the high temperature resistant fabric base, with a fabric weight of 80~300g / m². The high-temperature resistant fabric substrate is placed in deionized water and ultrasonically cleaned at room temperature for 10-15 minutes to remove surface slurry, oil and impurities. After cleaning, place the fabric base in an oven at 60-80℃ and dry for 20-30 minutes, controlling the fabric moisture content to be below 3%. Cool the dried fabric base to room temperature for later use.
[0008] Preferably, in step 2, the preparation of the shape memory modified liquid specifically includes the following steps: In an Erlenmeyer flask, polycarbonate diol was mixed with dehydrated N,N-dimethylformamide, heated in a water bath to 60-80°C and stirred until completely transparent. 4,4'-diphenylmethane diisocyanate was added and stirred for 20 min. Dibutyltin dilaurate was then added and heated in a water bath to 65°C and stirred for 3 h to obtain a prepolymer solution. In a separate beaker, hydroquinone dihydroxyethyl ether, 1,4-butanediol, trimethylolpropane and N,N-dimethylformamide were added, and the mixture was heated in a water bath to 65°C and stirred until completely transparent to obtain a chain extender crosslinking agent solution. The prepolymer solution was added dropwise to the chain extender / crosslinker solution at a rate of 1 drop / 5 seconds. During the addition process, the solution was heated to 60°C in a water bath and stirred for 2 hours to obtain a uniform and transparent shape memory polyurethane liquid. In a separate beaker, ammonium polyphosphate, pentaerythritol, melamine, and N,N-dimethylformamide were added. After mechanical stirring for 10 minutes, the mixture was ultrasonically dispersed in an ice-water bath for 30 minutes to obtain a uniform and stable flame retardant slurry. The shape memory polyurethane adhesive (SMPU) was cooled to 60°C and the flame retardant slurry was slowly added over 10 minutes with stirring. After the addition was complete, stirring was continued at 60°C for 1 hour to obtain a flame retardant shape memory polyurethane (FR-SMPU) blend. N,N-dimethylformamide was added to the flame-retardant shape memory polyurethane blend and stirred for 30 minutes. Then, the mixture was degassed under vacuum at 50°C for 15 minutes and filtered through a 200-mesh filter to obtain the flame-retardant shape memory modified liquid.
[0009] Preferably, the polar organic solvent is added to the activated molecular sieve at a mass ratio of N,N-dimethylformamide to activated molecular sieve of 3:1 to 8:1 before use for dehydration treatment, and the activated molecular sieve is pre-activated in a tube furnace at 200 to 300°C for 5 hours.
[0010] Preferably, the hydroquinone dihydroxyethyl ether is pre-dried in a vacuum oven at 60°C for 12 hours, the trimethylolpropane is pre-dried in a vacuum oven at 60°C for 8 hours, and the polycarbonate diol is pre-dehydrated in a vacuum oven at 80°C for 24 hours.
[0011] Preferably, the stirring speed during the preparation of the prepolymer solution is 300~500 r / min, and the order of addition is as follows: first add polycarbonate diol and N,N-dimethylformamide, and after they are completely dissolved, add 4,4'-diphenylmethane diisocyanate, and finally dibutyltin dilaurate. The total time for adding the prepolymer solution was controlled within 40 minutes. The entire adding and subsequent stirring process was carried out in a sealed container to prevent water from entering. The ultrasonic dispersion power was 300W. The filtration process uses a 200-mesh filter screen. After filtration, the filtrate is collected for later use. The filter cake is then washed with a small amount of N,N-dimethylformamide, and the filtrates are combined.
[0012] Preferably, step 3 specifically includes the following steps: The high-temperature resistant fabric substrate after the pretreatment in step 1 is completely immersed in the flame-retardant shape memory modified liquid obtained in step 2, and immersed for 1 to 10 minutes under a negative pressure of -0.02 to -0.05 MPa. After impregnation, the high-temperature resistant fabric substrate is removed and rolled with rollers to control the liquid retention rate of the fabric to 70%~85%. After rolling, let the high-temperature resistant fabric base stand for 10-20 minutes to allow any excess residual liquid to drip or seep out naturally. The impregnation treatment allows the modified liquid to penetrate into the fiber bundles and between individual fibers of the high-temperature resistant fabric substrate under negative pressure. The rolling process ensures that the modified liquid is evenly distributed inside and outside the fabric. The settling process allows the fibers to fully absorb the modified liquid and remove any entrained air bubbles.
[0013] Preferably, step 4 specifically includes the following steps: The high-temperature resistant fabric substrate treated in step 3 is placed in an oven for gradient temperature pre-drying: first dried at 60~80℃ for 2~5 minutes, then dried at 90~100℃ for 2~5 minutes, so that the moisture and solvent inside the fabric can slowly evaporate. The pre-dried fabric is placed at 120~150℃ for high-temperature curing and cross-linking for 3~8 minutes to allow chemical cross-linking reactions to occur between shape memory polyurethane molecular chains and fiber macromolecules, as well as between polyurethane molecular chains, in order to construct a three-dimensional polyurethane cross-linked network. After the high-temperature curing fabric is naturally cooled to room temperature, it is then placed at a constant temperature of 40~70℃ for 15~20 minutes to fully activate the reversible deformation structure of the molecular chain of shape memory polyurethane. The gradient heating pre-drying process avoids rapid film formation on the fabric surface to ensure uniform solvent escape from the interior, while the low-temperature constant-temperature activation treatment enables the polyurethane soft segment molecular chains to acquire reversible movement capabilities.
[0014] Preferably, in step 4, the process of in-situ crosslinking of shape memory polyurethane within the fabric fibers to form a stable and reversible memory network specifically includes the following steps: During the high-temperature curing and crosslinking process, the rigid benzene ring structural units provided by 4,4'-diphenylmethane diisocyanate are stacked in an orderly manner in the polyurethane hard segment microphase region to form a physical crosslinking lattice, which fixes the permanent shape of the fabric. During the low-temperature isothermal activation process, the flexible molecular chain segments provided by polycarbonate diol acquire sufficient chain segment mobility and undergo reversible intramolecular rotation and conformational transformation under external thermal stimulation, thereby achieving shape memory function. The trifunctional chemical crosslinking points provided by the trimethylolpropane, together with the chain extender, construct a covalent crosslinking network. This covalent crosslinking network is embedded between the hard segment microphase region and the soft segment microphase region of the polyurethane, inhibiting the irreversible slippage of the molecular chain during repeated deformation. The gradient heating and pre-drying process allows the polar organic solvent in the modified liquid to migrate and escape uniformly from the inside to the outside of the fiber, preventing the polymer from accumulating on the fiber surface. This ensures that the in-situ crosslinking reaction of the shape memory polyurethane occurs inside the fiber rather than just on the fiber surface.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. A method for preparing polyurethane shape memory fabric for fireproof materials involves introducing a phosphorus-nitrogen intumescent flame retardant into a shape memory polyurethane matrix. The flame retardant is uniformly dispersed within the polymer network through blending. The flame retardant does not participate in the crosslinking reaction and does not affect the integrity of the reversible phase structure of the polyurethane. At the same time, it imparts highly efficient flame retardant properties to the fabric. The shape memory polyurethane provides thermal deformation response capability, and the intumescent flame retardant forms a dense carbon layer when heated to play a role in heat insulation and oxygen barrier. The two work together to give the fabric both excellent thermal response deformation function and flame retardant protection function, meeting the dual requirements of fireproof materials for intelligent deformation and safety protection.
[0016] 2. This method for preparing polyurethane shape memory fabric for fireproof materials employs a negative pressure permeation impregnation process, allowing the modified liquid to penetrate deep into the interior of high-temperature resistant fiber bundles and between individual fibers under negative pressure. After in-situ cross-linking and curing, a dual anchoring effect of mechanical interlocking and chemical bonding is formed between the shape memory polyurethane and the fibers. This differs from traditional normal pressure coating, which only allows the resin to adhere to the fiber surface. Instead, it anchors the memory network inside the fiber body, maintaining a firm bond even after repeated washing. This effectively solves the problem of memory function decay or even failure in fireproof materials during service and maintenance.
[0017] 3. The method for preparing polyurethane shape memory fabric for fireproof materials introduces a trifunctional crosslinking agent to construct a suitable chemical crosslinking network. The covalent crosslinking points are embedded between the hard and soft microphase regions of polyurethane, effectively binding the irreversible slippage of polymer chains during repeated deformation. At the same time, the gradient pre-baking-high temperature curing-low temperature activation heat treatment process ensures the integrity and order of the reversible phase structure of polyurethane. After multiple thermal deformation cycles, the shape recovery function of the fabric remains stable, meeting the service requirements of fireproof equipment under repeated thermal response in high-temperature operating scenarios.
[0018] 4. The method for preparing polyurethane shape memory fabric for fireproof materials uses negative pressure impregnation to allow the modified liquid to penetrate and load into the fiber interior, rather than coating it on the fiber surface or filling the yarn gaps. Combined with a gradient pre-drying process, it avoids the rapid evaporation of solvents that would cause surface film formation, ensuring that the polymer cross-links and cures inside the fiber rather than blocking the fabric pores. The treated fabric retains the inter-yarn channels of the fiber substrate, has excellent breathability, and the resin loading inside the fiber makes the fabric soft to the touch, providing good wearing comfort and mobility for firefighters and other high-temperature workers. Attached Figure Description
[0019] Figure 1 This is a flowchart illustrating the preparation process of the shape memory fabric modification liquid of the present invention. Figure 2 This is a schematic diagram illustrating the working principle of the shape memory fabric of the present invention. Figure 3 This is a flowchart illustrating the shape memory fabric recovery process of the present invention. Detailed Implementation
[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0021] Example 1, please refer to Figures 1 to 3 A method for preparing polyurethane shape memory fabric for fireproof materials, comprising the following preparation steps: Step 1, Raw material pretreatment: (1) Dehydration of polycarbonate diol: Place polycarbonate diol in a vacuum oven at 80°C for 24 hours to dehydrate. The pressure of the vacuum oven is below -0.09 MPa. (2) Drying hydroquinone dihydroxyethyl ether and trimethylolpropane: Hydroquinone dihydroxyethyl ether was dried in a vacuum oven at 60°C for 12 hours, and trimethylolpropane was dried in a vacuum oven at 60°C for 8 hours. The pressure of the vacuum oven was below -0.09 MPa. (3) Activation of molecular sieve: The molecular sieve is placed in a tube furnace and heated to 250°C at a heating rate of 5°C / min, kept at the temperature for 5 hours, and then cooled to room temperature at a cooling rate of 5°C / min. (4) Dehydration with N,N-dimethylformamide: Mix N,N-dimethylformamide with the activated molecular sieve at a mass ratio of 5:1, let stand for 24 hours, and take the supernatant for later use. (5) Fabric substrate pretreatment: Polyimide plain weave fabric was selected as the high temperature resistant fabric substrate. The fabric weight was 200g / m², the warp and weft density was 170×170 threads / 10cm, and the specification was 10×3.5cm. The fabric was placed in deionized water and ultrasonically cleaned at room temperature for 15min to remove surface sizing, oil and impurities. Then it was placed in a 60℃ oven and dried for 28min to control the fabric moisture content to be below 3%. After taking it out, it was cooled to room temperature for use. Step 2, Preparation of flame-retardant shape memory modified liquid: (1) Preparation of prepolymer solution: 12g of polycarbonate diol and 80mL of dehydrated N,N-dimethylformamide were added to a conical flask, heated to 60℃ in a water bath and stirred at 500r / min until completely transparent; 6mL of 4,4'-diphenylmethane diisocyanate was added and stirred for 20min; then 0.25g of dibutyltin dilaurate was added, heated to 65℃ in a water bath and stirred for 3h to obtain the prepolymer solution; (2) Preparation of chain extender and crosslinker solution: Take another beaker and add 1.28g hydroquinone dihydroxyethyl ether, 1mL 1,4-butanediol, 0.1g trimethylolpropane and 50mL N,N-dimethylformamide. Heat in a water bath to 65℃ and stir until completely transparent to obtain chain extender and crosslinker solution; (3) Chain extension and crosslinking reaction: The prepolymer solution is added to the chain extension and crosslinking agent solution at a rate of 1 drop / 5 seconds. The total time of the addition is controlled within 40 minutes. During the addition process, the water bath is heated to 60°C and stirred for 2 hours. The entire addition and subsequent stirring process are carried out in a sealed container to prevent water from entering, so as to obtain a uniform, transparent, gel-free shape memory polyurethane liquid. (4) Preparation of flame retardant slurry: Take another beaker and add 1.2g ammonium polyphosphate, 0.4g pentaerythritol, 0.4g melamine and 20g N,N-dimethylformamide. After mechanical stirring for 10min, ultrasonically disperse in an ice-water bath for 30min with an ultrasonic power of 300W to obtain a uniform and stable flame retardant slurry. (5) Flame retardant blending modification: Cool the shape memory polyurethane adhesive to 60°C, slowly add the flame retardant slurry while stirring, and control the addition to be completed within 10 minutes. After the addition is completed, continue stirring at 60°C for 1 hour to obtain a flame retardant shape memory polyurethane blend. (6) Dilution, degassing and filtration: Add 70g of N,N-dimethylformamide to the flame-retardant shape memory polyurethane blend while stirring. After the addition is complete, continue stirring for 30min. Then degas at 50℃ under vacuum for 15min. Filter the degassed modified liquid through a 200-mesh filter, collect the filtrate, wash the filter cake with a small amount of N,N-dimethylformamide, and combine the filtrates to obtain the flame-retardant shape memory modified liquid.
[0022] Step 3, Negative pressure impregnation finishing: The pretreated polyimide fabric from step 1 is completely immersed in the flame-retardant shape memory modified liquid obtained in step 2. The fabric is immersed for 2 minutes under a negative pressure of -0.02 MPa to allow the modified liquid to penetrate into the fiber bundles and between individual fibers. After immersion, the fabric is removed and rolled with rollers to control the liquid content of the fabric to 70%~85%. The rolled fabric is left to stand for 10 minutes to allow excess residual liquid to drip or seep out naturally, and to allow the fibers to fully absorb the modified liquid and expel any entrained air bubbles. Step 4: Heat treatment for shaping. The fabric treated in step 3 was placed in an oven for gradient temperature pre-drying: first dried at 80℃ for 5 minutes, then dried at 100℃ for 2 minutes, allowing the internal moisture and solvent to evaporate slowly, avoiding rapid film formation on the fabric surface and ensuring uniform solvent escape; the pre-dried fabric was then placed at 140℃ for high-temperature curing and cross-linking for 5 minutes, allowing chemical cross-linking reactions to occur between the shape memory polyurethane molecular chains and fiber macromolecules, as well as between polyurethane molecular chains, to construct a three-dimensional polyurethane cross-linked network; the high-temperature cured fabric was then naturally cooled to room temperature, and then placed at 60℃ for constant-temperature activation treatment for 15 minutes, allowing the reversible deformation structure of the shape memory polyurethane molecular chains to be fully activated; thus, the polyurethane shape memory fabric for fireproof materials was obtained.
[0023] Example 2 differs from Example 1 only in that the negative pressure immersion time in step 3 is 5 minutes and the standing time is 10 minutes. The remaining steps are exactly the same as in Example 1.
[0024] Example 3 differs from Example 1 only in that the negative pressure immersion time in step 3 is 8 minutes and the standing time is 15 minutes. The remaining steps are exactly the same as in Example 1.
[0025] Comparative Example 1: This comparative example serves as a blank control group; only the fabric underwent the following operations: Step 1: Fabric pretreatment: Clean the 10×3.5cm polyimide fabric with deionized water at room temperature using ultrasonic cleaning for 15 minutes to remove surface sizing, oil, and impurities. Then dry it in a 60℃ oven for 28 minutes, controlling the fabric moisture content to be below 3%. Cool it to room temperature for later use. Step 2, Drying: The fabric pre-drying adopts a two-stage temperature program: drying at 80℃ for 5 minutes and drying at 100℃ for 2 minutes. Step 3, Curing: Place the fabric at a high temperature of 140℃ for 5 minutes to cure; Step 4, Low-temperature activation treatment: After the cured fabric cools naturally, activate it at a constant temperature of 60℃ for 15 minutes.
[0026] Comparative Example 2: In this comparative example, the fabric substrate pretreatment and modified liquid preparation steps are completely consistent with those in Example 1. The only difference is that the -0.02MPa negative pressure impregnation in the fabric impregnation step is changed to normal pressure impregnation. The remaining steps are completely consistent with those in Example 1.
[0027] The fabrics prepared in Examples 1 to 3 and Comparative Examples 1 and 2 were subjected to performance tests. The test items and test methods are as follows: Performance testing: 1. Shape recovery performance: The bending and wrinkle recovery test method is adopted. The activated experimental sample with a certain shape is cooled and pressurized. The sample with the initial flat shape is folded into a Miura fold shape and then cooled and pressurized. The cooling and pressurization time is 40 min. After the pressurization is completed, the sample is taken out and placed in a 60℃ oven for 15 min to observe the degree to which the sample recovers to the initial shape. The projected length of each shape is measured to calculate its shape recovery performance. The shape recovery performance is characterized by the shape recovery rate. 2. Flame retardant performance: The limiting oxygen index (LOI) test method is used to evaluate the flame retardant performance of the material by measuring the minimum oxygen concentration required for sustained combustion in an oxygen-nitrogen mixed gas flow environment. A 100mm×10mm strip sample is vertically fixed in the combustion chamber. The volume fractions of oxygen and nitrogen are adjusted to create different oxygen concentration environments. The upper part of the sample is ignited with a standard flame. The oxygen content is gradually adjusted until the sample can just maintain stable combustion. The oxygen volume fraction at this time is recorded as the limiting oxygen index (LOI value). The higher the LOI value, the less likely the material is to burn in air and the better the flame retardant performance. 3. Washing durability test: According to the washing procedure of GB / T 8629 standard, the fabric sample was washed 20 times with standard water. After washing, the shape recovery rate was tested according to the above method, and the retention rate was calculated. 4. Cyclic stability test: Repeat the above folding-pressurization-thermal recovery cycle 20 times and record the recovery rate each time; 5. Softness and Breathability Tests: Fabric softness is characterized using the bending length method. Samples are cut into strips of fabric of specified dimensions (usually 2.5cm × 25cm), and samples are taken along both the warp and weft directions. The samples are then conditioned under standard temperature and humidity conditions. During testing, the sample is placed flat on a horizontal platform, and one end is slowly pushed out freely, bending under its own weight. Pushing is stopped when the front end of the sample reaches a specified angle (usually 41.5°), and the cantilever length is recorded. Each group of samples is tested repeatedly, and the average value is taken. A shorter cantilever length indicates better fabric softness. Fabric breathability is tested according to GB / T 5453 using the pressure difference method. The fabric is cut into circular samples (diameter ≥ 10cm) and fixed in the test chamber of the breathability tester. Under constant pressure difference (usually 100Pa), the airflow rate through the fabric per unit time is measured, and the breathability rate is recorded. Each sample is tested repeatedly, and the average value is taken. A higher breathability rate indicates stronger air circulation and better breathability.
[0028] The performance of each set of examples and comparative examples is summarized in Tables 1 and 2: Table 1. Comparison of shape recovery performance between the examples and comparative examples.
[0029] Table 2 Comparison of other performance characteristics between the Examples and Comparative Examples
[0030] From the data in Tables 1 and 2, we can see that: 1. Excellent shape memory performance: The initial shape recovery rate of Examples 1 to 3 is ≥98.60%, with the highest reaching 98.96% (Example 2), which is significantly higher than that of the normal pressure impregnation comparative example (84.47%) and the blank control (22.5%), proving that the modified liquid and process of the present invention can endow polyimide fabrics with efficient and stable thermal response shape memory function; 2. Significantly improved washability: After 20 standard washes, the shape recovery rate retention of Examples 1-3 was ≥94.5%, with the best reaching 96.0% (Example 2); while the retention rate of Comparative Example 2 (atmospheric pressure impregnation) was only 75.16%. Negative pressure penetration allows the modified liquid to penetrate deep into the fiber and crosslink in situ, forming a dual anchoring effect of mechanical interlocking and chemical bonding, fundamentally solving the industry pain point of traditional coating peeling off during washing; 3. Outstanding thermal cycling stability: After 20 cycles of folding-pressurization-thermal recovery, the recovery rate of Examples 1-3 remained at 96.8%-97.5%, with a decrease of <2%; while that of Comparative Example 2 decreased to 78.58%, with a decrease of about 5.89%. The cross-linked network (TMP) effectively suppressed the irreversible slippage of molecular chains during repeated deformation, meeting the service requirements of fire protection equipment under multiple thermal deformations. 4. Excellent flame retardant performance: After adding APP / PER / MEL intumescent flame retardant, the limiting oxygen index (LOI) of Examples 1 to 3 reaches 32.5% to 33.5%, which is 4.5 to 5.5 percentage points higher than the original polyimide fabric (LOI≈28%), reaching the flame retardant level. Moreover, the flame retardant is uniformly dispersed in the polyurethane matrix without damaging the integrity of the memory network. 5. Excellent retention of softness and breathability: Example 2 (preferred solution) has a bending length of 3.5 cm and an air permeability of 165 mm / s, which are improvements of 27.1% and 37.5% respectively compared to the comparative example of normal pressure process (4.8 cm, 120 mm / s). Gradient pre-drying avoids surface film formation, and negative pressure impregnation allows the resin to be evenly loaded inside the fiber rather than clogging the yarn gaps, thereby maximizing the retention of the fabric's original softness and air permeability, significantly improving wearing comfort; 6. Process versatility and industrialization prospects: This method covers the complete solution process route from monomer polymerization to flame retardant modification. The parameters of each step are clear and controllable. Degassing and filtration ensure the uniformity and stability of the impregnation solution. The process is highly compatible with existing fire-retardant fabric finishing production lines. No new special equipment is required. It can realize the large-scale production of various high-temperature resistant fiber substrates such as polyimide and aramid. The folding pattern of the fabric in this invention can be selected according to the application scenario. Common folding structures include Miura fold, Kresling fold, and hexagonal honeycomb fold. This invention adopts Miura fold, mainly to take advantage of its excellent fold-to-unfold ratio, which can reach 25 times, greatly improving its storage capacity. Miura fold combined with fire-resistant shape memory fabric makes fire-resistant materials easy to carry and install. When exposed to high temperatures, it can automatically unfold several times, thereby achieving a fire-resistant effect, solving the drawbacks of traditional fire-resistant materials that occupy a lot of space and are inconvenient to carry.
[0031] In summary, this invention significantly outperforms the comparative examples (atmospheric pressure impregnation and blank control) in multiple dimensions, including shape memory recovery rate, washability, thermal cycling stability, flame retardancy, and softness and breathability. Among these, the impregnation time of 5 min (Example 2) is the optimal solution, exhibiting the best overall performance (recovery rate 98.96%, washability retention 96.0%, post-cycle retention 97.5%, LOI 33.4%, bending length 3.5 cm, and air permeability 165 mm / s). This invention provides a comprehensive, feasible, and industrially viable technical solution for the field of intelligent fireproof materials.
[0032] The above are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. The scope of protection of the present invention should be determined by the scope of protection of the technical solution.
Claims
1. A method for preparing polyurethane shape memory fabric for fire-retardant materials, characterized in that, Includes the following steps: Step 1: Prepare the base material for the polyurethane shape memory fabric, namely the high-temperature resistant fabric base, and clean and dry the high-temperature resistant fabric base to remove surface impurities and control the fabric moisture content to be lower than the set value for later use. Step 2: Dissolve polycarbonate diol in a polar organic solvent, add 4,4'-diphenylmethane diisocyanate and a catalyst to carry out a prepolymerization reaction to obtain a prepolymer solution. Separately, dissolve a chain extender and a crosslinking agent in a polar organic solvent, add the prepolymer solution to carry out a chain extension and crosslinking reaction to obtain a shape memory polyurethane adhesive. Disperse an intumescent flame retardant in a polar organic solvent to form a flame retardant slurry. Blend the flame retardant slurry with the shape memory polyurethane adhesive, and after degassing and filtration, obtain a flame retardant shape memory modified liquid. Step 3: Immerse the pretreated fabric substrate material from Step 1 in the flame-retardant shape memory modified liquid obtained in Step 2, and perform impregnation treatment under negative pressure to allow the flame-retardant shape memory modified liquid to penetrate into the fibers of the fabric substrate material. After removal, roll the material to control the liquid retention rate and let it stand to remove excess residual liquid. Step 4: The fabric treated in Step 3 is subjected to gradient heating pre-drying, high-temperature curing crosslinking and low-temperature constant temperature activation treatment in sequence, so that the shape memory polyurethane crosslinks in situ inside the fabric fibers to form a stable and reversible memory network, thus obtaining the polyurethane shape memory fabric used for fireproof materials.
2. The method for preparing a polyurethane shape memory fabric for fireproof materials according to claim 1, characterized in that: The shape memory modified liquid comprises the following raw material components in parts by weight: 5-20 parts polycarbonate diol, 6-12 parts 4,4'-diphenylmethane diisocyanate, 0.05-0.5 parts dibutyltin dilaurate, 130-500 parts N,N-dimethylformamide, 0.5-1.28 parts hydroquinone dihydroxyethyl ether, 1-5 parts 1,4-butanediol, 0.10-0.18 parts trimethylolpropane, 0.5-5 parts ammonium polyphosphate, 0.2-3 parts pentaerythritol, and 0.2-3 parts melamine; The N,N-dimethylformamide is a polar organic solvent, which is dehydrated by activated molecular sieve before use; the dibutyltin dilaurate is a catalyst; the chain extender is a compound of hydroquinone dihydroxyethyl ether and 1,4-butanediol; the trimethylolpropane is a crosslinking agent; and the intumescent flame retardant is a phosphorus-nitrogen intumescent system composed of ammonium polyphosphate, pentaerythritol and melamine.
3. The method for preparing a polyurethane shape memory fabric for fireproof materials according to claim 2, characterized in that: Step 1 specifically includes the following steps: Select polyimide plain weave fabric or aramid fabric as the high temperature resistant fabric base, with a fabric weight of 80~300g / m². The high-temperature resistant fabric substrate is placed in deionized water and ultrasonically cleaned at room temperature for 10-15 minutes to remove surface slurry, oil and impurities. After cleaning, place the fabric base in an oven at 60-80℃ and dry for 20-30 minutes, controlling the fabric moisture content to be below 3%. Cool the dried fabric base to room temperature for later use.
4. The method for preparing a polyurethane shape memory fabric for fireproof materials according to claim 2, characterized in that: In step 2, the preparation of the shape memory modified liquid specifically includes the following steps: In an Erlenmeyer flask, polycarbonate diol was mixed with dehydrated N,N-dimethylformamide, heated in a water bath to 60-80°C and stirred until completely transparent. 4,4'-diphenylmethane diisocyanate was added and stirred for 20 min. Dibutyltin dilaurate was then added and heated in a water bath to 65°C and stirred for 3 h to obtain a prepolymer solution. In a separate beaker, hydroquinone dihydroxyethyl ether, 1,4-butanediol, trimethylolpropane and N,N-dimethylformamide were added, and the mixture was heated in a water bath to 65°C and stirred until completely transparent to obtain a chain extender crosslinking agent solution. The prepolymer solution was added dropwise to the chain extender / crosslinker solution at a rate of 1 drop / 5 seconds. During the addition process, the solution was heated to 60°C in a water bath and stirred for 2 hours to obtain a uniform and transparent shape memory polyurethane liquid. In a separate beaker, ammonium polyphosphate, pentaerythritol, melamine, and N,N-dimethylformamide were added. After mechanical stirring for 10 minutes, the mixture was ultrasonically dispersed in an ice-water bath for 30 minutes to obtain a uniform and stable flame retardant slurry. The shape memory polyurethane adhesive was cooled to 60°C and the flame retardant slurry was slowly added over 10 minutes with stirring. After the addition was complete, stirring was continued at 60°C for 1 hour to obtain a flame retardant shape memory polyurethane blend. N,N-dimethylformamide was added to the flame-retardant shape memory polyurethane blend and stirred for 30 minutes. Then, the mixture was degassed under vacuum at 50°C for 15 minutes and filtered through a 200-mesh filter to obtain the flame-retardant shape memory modified liquid.
5. The method for preparing a polyurethane shape memory fabric for fireproof materials according to claim 4, characterized in that: Before use, the polar organic solvent is added to the activated molecular sieve at a mass ratio of N,N-dimethylformamide to activated molecular sieve of 3:1 to 8:1 for dehydration treatment. The activated molecular sieve is pre-activated in a tube furnace at 200 to 300°C for 5 hours.
6. The method for preparing a polyurethane shape memory fabric for fireproof materials according to claim 5, characterized in that: The hydroquinone dihydroxyethyl ether was pre-dried in a vacuum oven at 60°C for 12 hours, the trimethylolpropane was pre-dried in a vacuum oven at 60°C for 8 hours, and the polycarbonate diol was pre-dehydrated in a vacuum oven at 80°C for 24 hours.
7. The method for preparing a polyurethane shape memory fabric for fireproof materials according to claim 6, characterized in that: The stirring speed during the preparation of the prepolymer solution is 300~500 r / min, and the order of addition is as follows: first add polycarbonate diol and N,N-dimethylformamide, and after they are completely dissolved, add 4,4'-diphenylmethane diisocyanate, and finally dibutyltin dilaurate. The total time for adding the prepolymer solution was controlled within 40 minutes. The entire adding and subsequent stirring process was carried out in a sealed container to prevent water from entering. The ultrasonic dispersion power was 300W. The filtration process uses a 200-mesh filter screen. After filtration, the filtrate is collected for later use. The filter cake is then washed with N,N-dimethylformamide, and the filtrates are combined.
8. The method for preparing a polyurethane shape memory fabric for fireproof materials according to claim 2, characterized in that: Step 3 specifically includes the following steps: The high-temperature resistant fabric substrate after the pretreatment in step 1 is completely immersed in the flame-retardant shape memory modified liquid obtained in step 2, and immersed for 1 to 10 minutes under a negative pressure of -0.02 to -0.05 MPa. After impregnation, the high-temperature resistant fabric substrate is removed and rolled with rollers to control the liquid retention rate of the fabric to 70%~85%. After rolling, let the high-temperature resistant fabric base stand for 10-20 minutes to allow any excess residual liquid to drip or seep out naturally.
9. A method for preparing a polyurethane shape memory fabric for fireproof materials according to claim 2, characterized in that: Step 4 specifically includes the following steps: The high-temperature resistant fabric substrate treated in step 3 is placed in an oven for gradient temperature pre-drying: first dried at 60~80℃ for 2~5 minutes, then dried at 90~100℃ for 2~5 minutes, so that the moisture and solvent inside the fabric can slowly evaporate. The pre-dried fabric is placed at 120~150℃ for high-temperature curing and cross-linking for 3~8 minutes to allow chemical cross-linking reactions to occur between shape memory polyurethane molecular chains and fiber macromolecules, as well as between polyurethane molecular chains, in order to construct a three-dimensional polyurethane cross-linked network. After high-temperature curing, the fabric is naturally cooled to room temperature, and then placed at a constant temperature of 40~70℃ for 15~20 minutes to fully activate the reversible deformation structure of the molecular chain of shape memory polyurethane.
10. A method for preparing a polyurethane shape memory fabric for fireproof materials according to claim 9, characterized in that: In step 4, the process of in-situ crosslinking of shape memory polyurethane within the fabric fibers to form a stable and reversible memory network specifically includes the following steps: During the high-temperature curing and crosslinking process, the rigid benzene ring structural units provided by 4,4'-diphenylmethane diisocyanate are stacked in an orderly manner in the polyurethane hard segment microphase region to form a physical crosslinking lattice, which fixes the permanent shape of the fabric. The trifunctional chemical crosslinking sites provided by trimethylolpropane, together with the chain extender, construct a covalent crosslinking network. The gradient heating and pre-drying process allows the polar organic solvent in the modified solution to migrate and escape uniformly from the inside to the outside of the fiber.